Analysis of Scale Problem Using Acidizing Stimulation in Field Z Kalrez Petroleum (Seram) LTD - Idrus, Sumina (Journal of Petroleum and Geothermal Technology, 2024)
The annual decrease in production at well Z occurs due to scale deposits that impede fluid flow. Scale is a production problem due to the mixing of two types of water with different properties so that the solubility limit of the compound in the formation water is exceeded. To overcome the scale, stimulation is carried out with an acidizing method using a type of acid (HCL 10%). Evaluation was conducted to determine the effect of acidizing stimulation on scale based on productivity index (PI), inflow performance relationship (IPR) curve and comparison of stimulation methods. Evaluation of test results after acidizing stimulation of well Z experienced an increase in production. Productivity Index increased from 4.748 bbl/psi to 9.036 bbl/psi. Based on the IPR curve before acidizing, the maximum flow rate (Q max) = 324,107 bpd, increased to Qmax = 769,021 bpd.Keywords: Cost Benefit, Productivity Index, Scale, Acidizing Stimulation